2018
DOI: 10.1177/0954408918765289
|View full text |Cite
|
Sign up to set email alerts
|

Internal unsteady flow characteristics of centrifugal pump based on entropy generation rate and vibration energy

Abstract: The transient fluid exciting force induced by unsteady flow in the centrifugal pump is the only exciting force that cannot be effectively eliminated. In order to explore the vibration problem caused by unsteady flow in the centrifugal pump, the steady and unsteady numerical calculations of the internal flow in a centrifugal pump with low specific speed were carried out under different flow rate conditions. With volute circumferential pressure pulsation test, the accuracy of numerical calculations was verified.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
19
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 25 publications
2
19
1
Order By: Relevance
“…Zhao et al [7] analyzed the mechanism of pressure fluctuation and stall propagation caused by rotating stalls and found that flow separation occurred near the leading edge of the pressure surface and transformed into vortices along the channel. Jia [8] studied the transient fluid excitation force caused by the unsteady flow in a centrifugal pump and obtained that the internal flow loss and low-frequency vibration energy of the impeller varies with the flow conditions, showing similar changes. Ni [9] found that the coupling between the rotor-stator interaction and the collision of the fluid discharged from the diffuser with the circulating flow to the casing bottom is the main cause of the strong pressure pulsation.…”
Section: Introductionmentioning
confidence: 97%
“…Zhao et al [7] analyzed the mechanism of pressure fluctuation and stall propagation caused by rotating stalls and found that flow separation occurred near the leading edge of the pressure surface and transformed into vortices along the channel. Jia [8] studied the transient fluid excitation force caused by the unsteady flow in a centrifugal pump and obtained that the internal flow loss and low-frequency vibration energy of the impeller varies with the flow conditions, showing similar changes. Ni [9] found that the coupling between the rotor-stator interaction and the collision of the fluid discharged from the diffuser with the circulating flow to the casing bottom is the main cause of the strong pressure pulsation.…”
Section: Introductionmentioning
confidence: 97%
“…Most previous KED analyses for centrifugal pumps have focused on steady numerical results 15,16,18 and ignored the near-wall revised KED. 17,19,20 This study addresses these shortcomings. Energy loss is calculated by post-processing the 3D unsteady numerical results through KED theory, and the near-wall revised KED is considered.…”
Section: Introductionmentioning
confidence: 99%
“…Unstable flow structures, such as return vortex at the tongue, shedding vortex at the blade trailing edge and return vortex at the inlet or outlet, will occur in centrifugal pumps when they are operated under part-load conditions [4][5][6]. The rotor-stator interaction at the tongue and the shedding vortex at the blade trailing edge are the main causes of unstable pressure pulsation in centrifugal pumps [7,8]. The internal flow of centrifugal pumps is extremely complicated and is accompanied by a 3D transient unstable strong turbulent motion that is difficult to capture.…”
Section: Introductionmentioning
confidence: 99%